EVALUATION OF STUDENTS' E-LEARNING LEARNING OUTCOMES USING THE COURSE COMPLETION METHOD - Jemakmun, Jemakmun makmun; Rahmatullah, M.Taufik; Roni, Mukran (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2024)
The current development of internet technology has changed the direction of the learning system at both elementary and tertiary levels by means of online, blended learning, and e-learning. This research aims to determine and analyze the learning outcomes of students using course completion during lectures using the eLearning method. The research subjects are Bina Darma University students. Data collection was carried out in this research through observation and taking primary data from the e-learning system. The instruments in this research include the independent variable (X), which is report completion, and the dependent variable (Y), which is elearning learning outcomes. The resulting research results are: 1. There is a positive influence from the activity task variable on the student learning outcome variable, which is known to be active in carrying out the tasks in e-learning. 2. There is a positive influence from the material variable on the student learning outcome variable, which is known to be active in opening the material. provided in e-learning. Multiple linear regression tests result from the course completion variable on student learning outcomes. It can be concluded that there is a positive influence on the learning outcomes of variable Y from variable X. Students can also share information or opinions on various matters relating to the subject matter or assignments given by the lecturer. Apart from that, lecturers can place learning materials and assignments that students must complete in certain places in e-learning for students to access.